Acetylcholine receptor-reactive T and B cells in myasthenia gravis and controls. - Link, H (1991)
Myasthenia gravis (MG) is strongly associated with antibodies to acetylcholine receptor (AChR), whereas the extent of T cell involvement is not settled. The number of cells secreting interferon-gamma (IFN-gamma) in response to AChR during 48 h culture of blood mononuclear cells (PBL) may reflect AChR-reactive T cells. Using an immunospot assay, we detected such cells in 23 of 30 patients with MG at a mean number of 1 per 33.333 PBL. AChR-reactive T cells were also found in patients with other neurological diseases (OND) and in healthy subjects but at lower frequencies and numbers. The T cell response to purified protein derivative and to PHA, and also to two major myelin proteins (basic protein and proteolipid protein) did not differ between MG and the two control groups, underlining the specificity of an augmented T cell reactivity to AChR in MG. Evaluation of the B cell response by enumerating anti-AChR IgG antibody secreting cells revealed such cells in 27 of 28 patients with MG at a mean value of 1 per 14,085 PBL. Cells secreting anti-AChR antibodies of the IgA and IgM isotypes were also detected in MG, but less frequently, at lower numbers, and only in conjunction with IgG antibody secreting cells. Anti-AChR antibody secreting cells were also found among patient with OND and in healthy controls, but at lower frequencies and numbers. These data confirm that AChR is a major target for autoimmune response in MG.